Improving the Skills of Penataban Banyuwangi Flower Farmers Through the Application of Post-Harvest Technology: Peningkatan Keahlian Petani Bunga Penataban Banyuwangi Melalui Terapan Teknologi Pasca Panen - Tristi Indah Dwi Kurnia; Siti Lutfiah Anggraeni; Zainal Roisul Amin (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
One of the Penataban farmer groups is the Cahaya Sentosa Farmers Group, established in 2010. This group has 43 members and focuses on food crops and horticulture. Improper post-harvest flower handling often causes flowers to wilt quickly and become easily damaged during storage and shipping, thus reducing market demand. Partners need assistance in implementing innovative post-harvest management practices to stabilize and consistently absorb the price of cut flowers and flower stubble from Penataban. Furthermore, limited promotional strategies are also a concern. Marketing has so far been conducted directly at markets and through Google Maps. This community service activity aims to improve farmers' post-harvest management skills to extend the shelf life of flowers. Furthermore, this activity also provided farmers with education on how to process flower harvest residue through a distillation process using essential oil distillation equipment. Through this innovative and educational approach, this activity successfully increased the capacity and welfare of members of the Cahaya Sentosa Farmers Group. The implementation of post-harvest Standard Operating Procedures (SOPs) for flower processing, taught through hands-on practice, has been proven to improve flower quality and durability. This has significant potential to expand market share and stabilize selling prices, eliminating farmers' dependence on specific sales moments. The introduction of essential oil distillation as a solution for flower waste management opens up significant product diversification opportunities. This innovation not only creates a new, more stable source of income but also aligns with the principles of a circular economy that transforms waste into products with economic value.